Value co-production made easy: the role of fantastical thinking. (11th August 2020) - Addis, Michela; Miniero, Giulia; Ricotta, Francesco
Abstract : Purpose: The purpose of the paper is to investigate the role individual fantastical thinking (FT) plays in increasing the returns of value co-production by using technology-based services (TBSs). Design/methodology/approach: This research combines 3 laboratory experimental studies with a survey, collecting data from 373 participants in total. An ad hoc customization Web-based tool – TBS - was created for the purpose of the studies. Findings: FT increases the outcomes of value co-production via a chain reaction, as follows: FT increases the perceived ease of value-production; perceived ease of value coproduction increases enjoyment; enjoyment increases a broad range of key outcome variables of value co-production, namely, attitude and purchase intention toward the co-designed products; the number of interactions and time of interaction in the value co-production process, which measure its efficiency; expert perceived quality and novelty of the co-designed products; ordinary perceived quality and novelty, satisfaction and willingness to pay for the co-designed products. Research limitations/implications: The procedure to activate FT requires relatively long training for participants, which might reduce the applicability of the procedure in other settings. Practical implications: This study suggests a way to prevent failures in value co-production at the design stage mediated by TBSs. The proposed framework supports a decrease in task complexity for the consumer, thus reducing the stress experienced by participants. As a side effect, this study presents a useful framework to better highlight the benefits and costs associated with value co-production, thus making the return on investment measurement easier to perform. Originality/value: The relevance of the findings to existing marketing literature lies in the advancement of knowledge related to value co-production processes by introducing the role of FT, a cognitive process designed specifically for consumer research and marketing.